2005
DOI: 10.1002/bio.812
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence quenching of β‐carboline alkaloids in micellar media. A study to select the adequate surfactant to use in analytical techniques

Abstract: The study of fluorescence quenching of the fluorophores allows the localization of the alkaloids (harmane and harmine) in the micelles (SDS, CTAB, Brij-35) to be established. In aqueous micellar solutions (SDS and Brij-35) at pH 13.0, emission corresponding to the neutral or zwitterionic forms can be observed. In the presence of CTAB (pH = 13.0) it was possible to observe the emission of anionic form. These species are not present in buffered aqueous solutions at these pH values. Bromide ion was added to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Indole, furan, thiophene and benzene derivates 1 j-n were also synthesized to enlarge the chemical diversity of the library. Heteroaromatic b-carboline derivatives 1 o and 1 p were purposely designed with the aim to obtain potential fluorescent probes, owing to the excellent native fluorescence found in carboline systems [38] that has led to their use as probes for biomolecules. [39] To study the importance, if any, of an appropriate planar conformation of 1 a-p, some singly reduced (2 a-d, 2 jk, 2 q) and a saturated derivative (3 d) were also synthesized (structures given in Table 2).…”
Section: Design Rationalementioning
confidence: 99%
“…Indole, furan, thiophene and benzene derivates 1 j-n were also synthesized to enlarge the chemical diversity of the library. Heteroaromatic b-carboline derivatives 1 o and 1 p were purposely designed with the aim to obtain potential fluorescent probes, owing to the excellent native fluorescence found in carboline systems [38] that has led to their use as probes for biomolecules. [39] To study the importance, if any, of an appropriate planar conformation of 1 a-p, some singly reduced (2 a-d, 2 jk, 2 q) and a saturated derivative (3 d) were also synthesized (structures given in Table 2).…”
Section: Design Rationalementioning
confidence: 99%
“…Scrutiny of literature reports has revealed different prototropic studies of HAR, and other β‐carboline alkaloid analogues in various self‐assembled confined medium. Becker et al.…”
Section: Resultsmentioning
confidence: 99%
“…Confined environment plays a very crucial role on the photophysics of the fluorophore/drug molecule which has been well explored in the literature . Similarly, various photophysical studies of harmine have been reported in different confined systems like micelles, microemulsions and cyclodextrins ,. Notably, in all these reports the interconversion between the different prototropic forms have been studied mainly as a function of pH and the zwitterionic form has only been observed at basic pH.…”
Section: Introductionmentioning
confidence: 99%
“…Indole, furan, thiophene and benzene derivates 1 j – n were also synthesized to enlarge the chemical diversity of the library. Heteroaromatic β‐carboline derivatives 1 o and 1 p were purposely designed with the aim to obtain potential fluorescent probes, owing to the excellent native fluorescence found in carboline systems38 that has led to their use as probes for biomolecules 39. To study the importance, if any, of an appropriate planar conformation of 1 a – p , some singly reduced ( 2 a – d , 2 j – k , 2 q ) and a saturated derivative ( 3 d ) were also synthesized (structures given in Table 2).…”
Section: Design Rationalementioning
confidence: 99%